The Water Supply of Ancient Rome : City Area, Water, and Population - Kleijn, G. de (Dutch Monographs on Ancient History and Archaeology, 2001)
Kleijn, G. de The Water Supply of Ancient Rome. City Area, Water, and Population. 2001 The Aqua Appia (312 BC) was the first of the eleven aqueducts leading to Rome to be built in antiquity. Time and again, the volume of water brought into the city was increased through the construction of new aqueducts. Rome's population and the extent of its built-up area also changed over time. This study examines how data derived from our knowledge of the urban water supply in antiquity may help answering questions about the urban social fabric and topography. DMAHA 22 (2001), 365 p. Cloth. - 68.00 EURO, ISBN: 9050632688.